UKRANIAN PROBLEM IN THE CONTEXT OF THE MODERN RUSSIAN ETHNIC POLICY - A. P. Koshkin; V. V. Cherdantsev (Russian Journal of Economics and Law, 2015)
Objective: to define the balance between ethnic and national policy in the Russian ethnic policy under the systemic crisis in Ukraine. Methods: the need to research the conceptual apparatus of the Russian ethnic politology and its adequacy to the modern Russian policy when analyzing the Ukrainian problem, the tendency to show the trend of development of ethnic political situation in Ukraine from the first to the second Maidan, determined the implementation of historical-genetic, comparative-historical and typological methods in their interaction. Results: the efficiency of the two-level model of the processes of interethnic interaction was shown: basically primordial factors of ethnical identity are exposed to the directed influence of constructed ethnicity, leading the ethnos to the political mobilization and changing its primary characteristics. During the decade from the first and second Maidans, the forming of national Ukrainian identity as anti-Russian one entered the new phase. Obtaining the systemic unity of ethnic and national policy of Russia is intended to promote the adequate response to this challenge. Scientific novelty: the article reveals the inconsistency of unilateral domination of post-modern approach to the ethnos and ethnicity. It states the necessity of the optimal combination of primordial basis of the ethnos and the constructivist tactical flexibility when solving the certain ethnic political problems under the Ukrainian crisis. Practical value: the main provisions and conclusions of the article can be used in scientific and educational activity, when researching the ethnos and ethnicity, when analyzing the ethnic political processes in the modern Ukraine and viewing the condition and prospects of development of Russian-Ukrainian relations.